2008
DOI: 10.1080/00071660802236021
|View full text |Cite
|
Sign up to set email alerts
|

Dietary selenium increases vitamin E contents of egg yolk and chicken meat

Abstract: 1. The influence of different forms of dietary selenium (Se) on vitamin E (alpha-tocopherol) and Se contents of egg yolk and chicken meat was investigated. 2. Eggs were collected from laying hens subjected to 4 different dietary treatments after 24 weeks of age. Treatments compared the effects of inorganic Se supplementation (selenite) to those of organic (Se-enriched yeast, Se-enriched alga Chlorella) supplements. In a second experiment the effect of the above organic dietary Se supplementation on the alpha-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 30 publications
4
23
0
Order By: Relevance
“…Selenium increased the α-tocopherol content in egg yolks, as shown in previous studies by Surai (2000) and Skřivan et al (2008b). The effect of Semethionine on α-tocopherol concentration was more pronounced than that of sodium selenite, and was statistically significant.…”
Section: Selenium and α-Tocopherol Concentration In Eggssupporting
confidence: 58%
“…Selenium increased the α-tocopherol content in egg yolks, as shown in previous studies by Surai (2000) and Skřivan et al (2008b). The effect of Semethionine on α-tocopherol concentration was more pronounced than that of sodium selenite, and was statistically significant.…”
Section: Selenium and α-Tocopherol Concentration In Eggssupporting
confidence: 58%
“…Beef is a major source of dietary selenium for humans (Zhang et al, 2010) and the result of the present study indicated that the prolonged supplementation with organic Se (Se-Y) is more effective to increase Se concentration in muscle tissue than inorganic Se. The efficacy of Se yeast to enrich the trace mineral content in meat has been reported not only in beef (Juniper et al, 2008b) but also in veal (Skřivanová et al, 2007), lamb (Vignola et al, 2009), chicken (Skrivan et al, 2008) and pork (Mahan et al, 1999). According to Juniper et al (2008b), the greater concentration of Se in the muscle tissue of bulls offered organic Se when compared with NaSe might arise from an enhanced availability and tissue retention of the trace element.…”
Section: Discussionmentioning
confidence: 99%
“…Both vitamin C and Se increased vitamin E deposition in the egg yolk. The sparing effect of Se on the amount of vitamin E in eggs has been described previously (Surai, 2000;Skřivan et al, 2008). Vitamin C can reduce tocopheryl radicals formed in reactions with reactive oxygen species; in our previous experiment, however, no sparing effect of vitamin C on the amount of vitamin E in the meat of broilers was apparent (Skřivan et al, 2012).…”
Section: Discussionmentioning
confidence: 55%
“…Selenium (Se) is an essential trace element that is required for the activity of selenoproteins involved in antioxidant defence, thyroid hormone deiodination, and other vital physiological functions (Surai, 2006). Several authors have studied the effect of a combination of Se and vitamin E on the antioxidative system in broiler chickens (Surai, 2000;Skřivan et al, 2008;Kim et al, 2010) and laying hens (Skřivan et al, 2010). Skřivan et al (2012) investigated the combined effect of dietary vitamin C and Se on the composition and oxidative stability of the meat of broiler chickens.…”
mentioning
confidence: 99%